Family-centered approach to stunting reduction: assessing the effectiveness of culturally-tailored interventions among Moi Families in Southwest Papua - Maria Loihala; Indar Indar; Aminuddin Syam; Muhamad Syafar (Universitas Airlangga, 2026)
Introduction: Stunting remains a significant public health challenge in Indonesia, particularly in geographically isolated regions like Southwest Papua, where cultural practices and socioeconomic factors contribute to high prevalence rates. The Moi ethnic group in Sorong Regency faces unique barriers, including food taboos, limited nutritional diversity, and inadequate breastfeeding practices, which conventional interventions often fail to address effectively. This study aimed to analyze the influence of the Family Transcultural Module (FTM) on family care practices and support systems for stunting treatment among the Moi ethnic group in Sorong Regency, Southwest Papua.Methods: A community-based intervention study with a pre-post design was conducted from January to May 2024 across five districts in Sorong Regency. A total of 132 Moi families with children aged 0-24 months at risk for stunting were recruited using purposive sampling and equally assigned to intervention (n=66) and control (n=66) groups. The intervention group received the Family Transcultural Module with educational leaflets, while the control group received only the FTM. Data were collected at baseline (pre-test), immediately after intervention (post-test 1), and one month following intervention (post-test 2) using standardized questionnaires measuring parenting practices and family support. Statistical analysis included descriptive statistics, the Wilcoxon signed-rank test, and the Mann-Whitney U test with a significance set at P-value< .05.Results: Most mothers in both groups were aged 31-40, with limited formal education and high employment rates (77.3% intervention, 78.8% control). Both intervention approaches demonstrated significant improvements in parenting practices (from a mean of 9.80±4.90 at baseline to 16.96±4.90 at post-test 2, P-value< .001, Cohen's d=1.46) and family support scores (from 27.96±12.04 to 40.73±14.85, P-value< .001, d=1.06). Within-group improvements demonstrated large effect sizes, while between-group comparisons revealed small to negligible effect sizes (d= .02- .35). No significant differences were found between the intervention and control groups at any measurement point, suggesting comparable effectiveness of the core FTM component regardless of supplementary educational materials.Conclusion: The Family Transcultural Module effectively improved parenting practices and family support among Moi ethnic families, demonstrating the importance of culturally-adapted interventions for stunting prevention in indigenous communities. The FTM successfully addressed key behavioral determinants of stunting despite challenging socioeconomic contexts by engaging with existing family structures and cultural values. These findings suggest that culturally-embedded, family-centered approaches can overcome specific implementation barriers and potentially contribute to sustainable stunting reduction in vulnerable populations.Keywords: stunting prevention; family transcultural module; indigenous health; parenting practices; family support; moi tribe